(untitled) (Conferencea, 2022)
The article focuses on the importance of the formation of ecological thinking of young schoolchildren in the views of Al-Khwarizmi and Al-Farobi, the principles of selection of materials on the content of these sources, as well as the emergence and strengthening of behavioral qualities in the formation of ecological thinking and culture in young minds, arousing love for the environment, conservation of nature, aimed at the formation of austerity, are reflected as the main problems of our time.